Albuminuria, the High-Density Lipoprotein Proteome, and Coronary Artery Calcification in Type 1 Diabetes Mellitus - Shao, Baohai; Zelnick, Leila R; Wimberger, Jake; Himmelfarb, Jonathan; Brunzell, John; Davidson, W Sean; Snell-Bergeon, Janet K; Bornfeldt, Karin E; de Boer, Ian H; Heinecke, Jay W (Arteriosclerosis, thrombosis, and vascular biology, 2019)
Objective- Albuminuria is an important risk factor for cardiovascular disease in diabetes mellitus. We determined whether albuminuria associates with alterations in the proteome of HDL (high-density lipoprotein) of subjects with type 1 diabetes mellitus and whether those alterations associated with coronary artery calcification. Approach and Results- In a cross-sectional study of 191 subjects enrolled in the DCCT (Diabetes Control and Complications Trial)/EDIC study (Epidemiology of Diabetes Interventions and Complications), we used isotope dilution tandem mass spectrometry to quantify 46 proteins in HDL. Stringent statistical analysis demonstrated that 8 proteins associated with albuminuria. Two of those proteins, AMBP (α1-microglobulin/bikunin precursor) and PTGDS (prostaglandin-H2 D-isomerase), strongly and positively associated with the albumin excretion rate ( P<10 ). Furthermore, PON (paraoxonase) 1 and PON3 levels in HDL strongly and negatively associated with the presence of coronary artery calcium, with odds ratios per 1-SD difference of 0.63 (95% CI, 0.43-0.92; P=0.018) for PON1 and 0.59 (95% CI, 0.40-0.87; P=0.0079) for PON3. Only 1 protein, PON1, associated with both albumin excretion rate and coronary artery calcification. Conclusions- Our observations indicate that the HDL proteome is remodeled in type 1 diabetes mellitus subjects with albuminuria. Moreover, low concentrations of the antiatherosclerotic protein PON1 in HDL associated with both albuminuria and coronary artery calcification, raising the possibility that alterations in HDL protein cargo mediate, in part, the known association of albuminuria with cardiovascular risk in type 1 diabetes mellitus. Visual Overview- An online visual overview is available for this article.